Insight into functionalized-macrocycles-guided supramolecular photocatalysis - Zuo, Minzan; Velmurugan, Krishnasamy; Wang, Kaiya; Tian, Xueqi; Hu, Xiao-Yu (Beilstein Journal of Organic Chemistry, 2021)
Due to the unique characteristics of macrocycles (e.g., the ease of modification, hydrophobic cavities, and specific guest recognition), they can provide a suitable environment to realize photocatalysis via noncovalent interactions with different substrates. In this minireview, we emphasized the photochemical transformation and catalytic reactivity of different guests based on the binding with various macrocyclic hosts as well as on the role of macrocyclic-hosts-assisted hybrid materials in energy transfer. To keep the clarity of this review, the macrocycles are categorized into the most commonly used supramolecular hosts, including crown ethers, cyclodextrins, cucurbiturils, calixarenes, and pillararenes. This minireview not only summarizes the role that macrocycles play in photocatalytic reactions but also clarifies the photocatalytic mechanisms. Finally, the future research efforts and new pathways to apply macrocycles and supramolecular hybrid materials in photocatalysis are also discussed.
Keywords: host–guest chemistry; macrocycles; noncovalent interactions; supramolecular photocatalysis